July 2011 DMM Podcast: an interview with Ruslan Medzhitov (The Company of Biologists, 2011)
SUMMARY This podcast includes excerpts from an interview with Ruslan Medzhitov, of Yale University, in which he discusses the early years of his career and explains what he considers the three most important issues in immunological research today. Narrated by Sarah E. Allan. To view this podcast, visit http://www.biologists.com/DMM/podcasts/index.html.